Olfactory Function After Surgical Treatment of CRS: A Comparison of CRS Patients to Healthy Controls - Mattos, Jose L. (Am J Rhinol Allergy, 2020)
BACKGROUND: Many patients with chronic rhinosinusitis (CRS) have persistent olfactory dysfunction (OD) following endoscopic sinus surgery (ESS). Few studies compare outcomes to control subjects so it is unknown if residual OD is due to persistent CRS. OBJECTIVE: Compare postoperative measures of OD in case patients with CRS to healthy controls without sinonasal disease. METHODS: Prospective, observational, multicenter cohort study between October, 2016 and May, 2019. Case participants were selected from referred adult patients diagnosed with CRS, with or without nasal polyposis (NP), electing ESS as subsequent treatment modality. Controls voluntarily enrolled from a community-based sample without a history of CRS. Primary outcomes included measures of preoperative and postoperative OD using “Sniffin’ Stick” pens which summarize odorant threshold (T), discrimination (D), and identification (I) scores. Secondary outcomes included the Questionnaire of Olfactory Disorders-Negative Statements (QOD-NS) survey and olfactory cleft endoscopy scores (OCES). RESULTS: Outcomes were compared between 113 cases and 164 controls of similar average age and gender. Cases reported significantly worse baseline Sniffin’ Sticks TDI total scores (−6.8[SE ± 1.0]; 95% CI: −4.9 to −8.7), QOD-NS (8.9[SE ± 1.1]; 95% CI: 6.8–10.9), and OCES (3.5[SE ± 0.4]; 95% CI: 2.9–4.2) on average. Cases reported significant postoperative improvement in TDI total score (3.7[SD ± 8.2]; 95% CI: 2.2–5.2), QOD-NS (−5.9[SD ± 8.7]; 95% CI: −7.6 to −4.3), and OCES (−1.7[SD ± 3.8]; 95% CI: −2.7 to −0.8) on average, while 63% of anosmics reported improved postoperative olfaction. Multivariate regression identified that NP (OR = 0.4; 95% CI: 0.2–1.0) and previous ESS (OR = 0.3; 95% CI: 0.1–0.8) decreased the odds of postoperative improvement equal to mean TDI scores of controls, while septoplasty increased those odds (OR = 4.5; 95% CI: 1.5–13.7). CONCLUSION: ESS improved olfactory metrics and restored olfactory function in approximately 50% of patients with CRS to that of healthy controls. Concurrent septoplasty increased the likelihood of achieving normal olfaction, while NP and previous ESS decreased those odds.